Cultivation of phototrophic microorganisms in photobioreactors illuminated via Wireless Light Emitter - Heining, Martin; Sutor, Alexander; Lindenberger, Christoph; Stute, Stephanie; Buchholz, Rainer (10th European Symposium on Biochemical Engineering Sciences and 6th International Forum on Industrial Bioprocesses, 2014)

Internal Illumination of photobioreactors via Wireless Light Emitter – a proof of concept - Heining, Martin; Sutor, Alexander; Lindenberger, Christoph; Stute, Stephanie; Buchholz, Rainer (Young Algaeneers Symposium, 2014)

Internal illumination of photobioreactors via wireless light emitters: a proof of concept - Heining, Martin; Sutor, Alexander; Stute, Stephanie; Lindenberger, Christoph; Buchholz, Rainer; Buchholz, Rainer (Journal of Applied Phycology, 2015)
A novel concept for internal illumination of photobioreactors via wireless light emitters (WLEs) has been developed to increase the manageable culture volume of photosynthetic active microorganisms or cells. The illumination system is based on free suspendable light emitters, which are powered wirelessly by near-field resonant inductive coupling and, therefore, are able to illuminate a photobioreactor more homogeneously than external illumination systems. Since an intermediate frequency electromagnetic field (IF-EMF) acts inside the reactor, the impact of an IF-EMF (B = 0.95 mT, f = 178 kHz) on the green alga Chlamydomonas reinhardtii is determined. The growth rate, the achieved cell dry weight, and the maximum photosynthetic yield Y (0) are unaffected by the applied IF-EMF. Furthermore, a negative effect of the potentially occurring mechanical stress due to the suspended WLE can be excluded. A culture which is mechanically stressed by 125 WLEs per liter shows the same maximal growth rate of 2.29 day(-1) as a control culture. Finally, the comparison of an externally illuminated photobioreactor and a via WLE internally illuminated photobioreactor shows the same growth rates in the exponential growth phase. However, the growth rate in the linear phase is more than twice the rate of the externally illuminated control culture, resulting in a more than 80 % higher achieved biomass. Light profiles over the cross section of both reactor types show clearly that the internal illumination via WLE results in a more uniform light distribution and a higher average light intensity in the reactor.
Keywords: Photobioreactor; Internal illumination; Wireless light emitter; Magnetic field; Wireless energy transfer; Near-field resonant inductive coupling

Raman Spectrocopy for non-invasive online measuerements of the pH and CO2 concentration in algal cultivations - Koch, Hanna; Noack, Kristina; Stute, Stephanie; Buchholz, Rainer; Will, Stefan (3rd European Congress of Applied Biotechnology (ECAB), 2015)